Storytelling: A Pedagogical Transformation in the Digital Age in Christian Religious Education - Jofrito Helong (Indonesian Journal of Christian Education and Theology, 2026)
This article discusses pedagogical transformation in Christian Religious Education through the use of digital storytelling in the digital era. Technological developments have significantly changed the learning patterns of contemporary students, making conventional one-way teaching approaches increasingly ineffective. This study employs a qualitative-descriptive method through a literature review to analyze the role of digital storytelling as a transformative learning medium in faith and character formation. The findings reveal that digital storytelling creates a more interactive, participatory, and contextual learning environment by integrating narratives, visuals, audio, and spiritual reflection. This approach not only enhances students’ cognitive understanding but also strengthens their affective and spiritual dimensions holistically. Furthermore, the concept of Digital Faith Formation demonstrates that faith development can occur within participatory and collaborative digital spaces.